Assessing the effect of regular swimming exercise on the micro- and macrovascular physiology of older adults (ACELA II study) - Klonizakis, M.; Mitropoulos, A. (Frontiers in Physiology, 2023)
Introduction: Cardiovascular disease (CVD) remains the number one death cause in the Western world. Our recent findings demonstrate potential CVD risk-reduction for older adults who undertake regular aquaticswimming exercise. Nevertheless, it remains unknown whether an exercise intervention, based on aquaticswimming exercise is feasible and effective prior to a wider implementation of a CVD-risk prevention strategy.Methods: This was a pragmatic, 2-group, randomised controlled trial. Forty older adults were randomly split into two groups (n=20 per group). The aquaticswimming exercise group consisted of participants that engaged in aquaticswimming exercise (2-3d/week, for 8 weeks). The control group did not perform any exercise. Flow mediated dilation percentage of difference (%FMD) was the primary outcome. Secondary outcomes included raw cutaneous vascular conductance (CVC). Feasibility outcomes (e.g., recruitment, adherence, and attrition rates) were also assessed.Results: Statistically significant macrovascular (%FMD; AquaticSwimming group: 9.8 ± 4.2%, p<0.001; Control group: 4.6 ± 2.5%) and microvascular function (RAW CVC; AquaticSwimming group: 4.1 ± 0.9, p<0.01; Control group: 3.2 ± 1.1) improvements were observed at the aquaticswimming group in comparison to control. Compliance to the twice and thrice weekly in an 8-week aquaticswimming exercise was 92.6% and 88.4%, respectively, with no dropouts.Our 8-week, community-based, pragmatic aquaticswimming exercise intervention is a feasible and effective exercise programme that could be implemented in older adults for the prevention of age-related cardiovascular diseaseCVD. These findings suggest that aquaticswimming exercise could significantly reduce the CVD risk in older adults and a large research clinical trial is warranted to establish these findings.